Portfolios reflexivos na formação inicial de professores: um estudo na formação inicial de professores de Biologia e Geologia ao nível do estágio pedagógico integrado - Grilo, João Maria Aranha (2002)
A presente investigação procura explorar implicações do uso de portfólios reflexivos na formação inicial de professores, na realidade sociocultural específica do nosso país, fazendo-o quer da perspectiva do professor em formação, quer da perspectiva da instituição que opta pela sua implementação. No ano lectivo 2000/01, os professores de um Núcleo de Estágio da Licenciatura em Ensino de Biologia e Geologia da Universidade de Évora desenvolveram um portfólio reflexivo como parte da sua formação e avaliação. O portfólio substituiu o dossier de estágio. Foi usado como modelo o Science Teaching Portfolio do BEST Profiram do Connecticut State Department of Education (EUA). A promoção de uma prática reflexiva e o contributo para uma avaliação mais formativa, autêntica, dinâmica e participada, parecem ser, para o professor em formação, as principais vantagens desta metodologia. A instituição de formação deve proceder a uma implementação cuidada que envolva a clara definição de objectivos, estrutura e formas de avaliação do portfólio, num processo negociado que apele à colaboração entre todos os intervenientes e em que a adequada formação destes assume um papel crucial. *** - Abstract - Reflective Portfolios in Initial Teacher Education a Study with Biology and Geology Teachers at the Student Teaching Level: - The objective of this study is to explore the implications of reflective portfolios use in Initial teacher training in the Portuguese sociocultural reality. These implications were studied from two different perspectives: the student teachers perceptions of the portfolio development process and the institution perceptions about portfolios in is Initial teacher training program. In the 2000-2001 school years, four placement teachers in their Initial teaching training course for Biology and Geology teachers at the Universidade de Évora have developed reflective student teaching portfolios as an assessment tool. The portfolio entered the training program as a replacement for the traditional teaching dossier. We have used the Science Teaching Portfolio of the Beginning Educator Support and Training (BEST) Program, Connecticut State Department of Education (EUA), as a model. Promotion of reflective practice and contribution to a more formative, authentic, dynamic and collaborative assessment seems to be the major positive outcomes to the student teacher. At the institution level, the process of implementing a portfolio must be carefully prepared. It demands a clear definition of gools, guidelines and assessment criteria. It must be a negotiated process that appeals to collaborative work and involves specific training of students and mentors.